Analysis of Green Bean Sprout Marketing Efficiency in Punia Village, Mataram City - Kurahman, Fatwa; Herdiana, Herdiana; Nirmawati, Nirmawati (Transforma Jurnal Manajemen, 2023)
Marketing is a human activity to satisfy needs and wants through the process, offering and exchanging (value) products with others. In this case, the supplier of mung bean sprouts came from the mung bean sprouts agro-industry in Punia Village, Mataram City. The marketing process of mung bean sprouts from the mung bean sprouts agro-industry will experience a long process and will experience price changes from the mung bean sprouts agro-industry to consumers through existing marketing agencies. The method used in this study is a quantitative descriptive method, namely the method used to solve problems that occur at the present time by collecting data, compiling, analyzing, and drawing conclusions and interpreting. The results of this study indicate that the marketing of mung bean sprouts has two marketing patterns that occur, namely: 1). Mung bean sprouts agroindustry – Retailers – Consumers, 2). Mung bean sprout agro-industry – Wholesalers – Retailers – Consumers. The marketing margin for the first channel is Rp.1,071 with an efficiency of 70% and the margin for the second channel is Rp. 1,571 with an efficiency of 30%, this shows that the two marketing channels are efficient. The two marketing channels for mung bean sprouts in Punia Village, Mataram City are efficient channels. But the most efficient channel is marketing channel I because the percentage in marketing channel I is as much as 70% and the channel used is shorter.